Documentación de la Norma Técnica Colombiana ISO 9001:2008 en el Jardín Botánico del Quindío (2015)
The Jardín Botánico del Quindío basically considered to establish a Quality Management System, with the purpose of achieving a better internal organization, a continuous improvement in the tasks development, a production increase, a working risks decrease and the process optimization to guarantee and ensure a high standard quality for the local and international users. On this sense, the Jardín Botánico del Quindío has initially considered to write the documents related with Colombian Technical Normative CTN ISO 9001 based on Quality Management Systems, with the objective of a better standardizing for the processes and procedures, increase the user´s satisfaction and continuously search the enforcement of its image as a touristic institution. Given these aspects, internship consists in making the documentation process of the Quality Management System, according to the requirements from the mentioned Technical Normative, starting with a diagnosis of the current institutional situation, working in the strategic direction and the processes characterization to close with the making of different forms, procedures and documents that allow to have an initial base for a future implementation of the Quality Management System (QMS).